Association between Mother's Educational Status And Home Literacy Environment With The Language Abilities Of Seven Year-Old Children: Path Analysis Evidence - Anggi Resina Putri; Nadya Susanti (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Factors that can influence the success of the educational process are family environmental factors, school environment, and community environment. The role of parents is to provide materials and help their children when they experience difficulties in the learning process. Language skills emerge in early childhood and are critical in promoting later literacy competencies, such as reading and writing. The period from birth to age 3 is critical for language development, as nearly all typically developing children acquire important language skills by age 3. During this period, children's home environment is especially important, as parents are the main providers of language input and support, allowing most children to acquire a basic foundation of language.Methods: This study used a cross sectional study design, which was conducted in Surakarta City. A sample of 100 people was selected using a random sampling technique. Data collection was performed using a questionnaire and analyzed by path analysis.Results: The direct relationship between expressive language abilities of children who have mothers with higher education is 2.2 units higher than children with mothers with low education (b=2.2; 95% CI= 0.9 to 3.5; p= 0.001). A high home literacy environment had a log odd of experiencing good expressive language skills of 2.04 units higher than children with a low home literacy environment (b=2.04; 95% CI= 0.7 to 3.3; p= 0.002). The indirect relationship between maternal higher education and expressive language abilities through the child's home literacy environment is statistically significant. Children who have mothers with higher education have log odd for high language expressive abilities of 2.8 units higher than children with mothers with low education (b=2.8; 95% CI= 1.7 to 3.9; p= <;0.001). Conclusion: A child's good expressive language abilities are influenced indirectly by the mother's high education through a high home literacy environment.